Penerapan Sistem Good Manufacturing Practices (GMP) Pada Proses Pembekuan Ikan Layur DI CV. Sinar Harapan Berau - Surya, Dwi Agus Ade; Zuraida, Ita; Pamungkas, Bagus Fajar; Irawan, Irman; Kusumaningrum, Indrati (Universitas Negeri Gorontalo, 2024)
The freezing industry requires a basic eligibility program to provide guarantees for a food safety system. The application of GMP or Good Manufacturing Practices in the food industry is a requirement to produce products that are safe for consumption. The aim of the study was to examine the application of GMP in freezing layur fish at CV. Sinar Harapan Berau and identify non-compliance factors in the implementation of GMP. The results showed that the application of GMP in CV. Sinar Harapan Berau has largely complied with the CPPOB guideline requirements. Based on the analysis of non-conformity, there are 14 aspects that are suitable and 4 aspects that are not suitable with the percentages of 77.8% and 22.2%, respectively. Several factors cause non-compliance with GMP, namely puddles of water on the road leading to the production site, the road has not been cemented, and without laying stones. There are no washing facilities in the toilet area, there is still rust on the tables and pans in the production area. CV. Sinar Harapan also does not yet have laboratory facilities for quality control and safety of raw materials, but only inspects organoleptically.